Developing Integrated Smartphones Notification of Server Resource Monitoring System Using Zabbix, Webhook, and Telegram - Sulasno Sulasno; Rakhmat Saleh; Intan Savitri (Department of Informatics Engineering, Universitas Muhammadiyah Purwokerto, 2021)
Server monitoring activities are important to ensure the availability of resources used for the execution of its internal processes. Generally, Administrators monitor the use of server resources through a computer using a browser. The problem with monitoring through a computer is less flexible and slow for checking notifications about the state of problem server resources in real-time anytime and anywhere using smartphones. This study aims to develop notification integration on smartphones from a server resource monitoring system using Zabbix Webhook and Telegram. The research method used is the Cisco PPDIOO Lifecycle Approach to Network Design and Implementation. As a case study, it is located at the Center for Empowerment of Informatics and Nuclear Strategic Area, the National Nuclear Energy Agency. The results of the study are notifications on smartphones via the Telegram bot account indicating a problem with resource usage. The results of this study have been used by server Administrators. The server Administrators have provided information about the benefits of this system, for flexibility, speed of getting information in resource usage, identifying, and resolving problems before there are complaints so that the quality of service is getting better.